Bunny cakes - Wells, Rosemary (New York : Dial Books for Young Readers, 1997)
Max makes an earthworm cake for Grandma's birthday and helps Ruby with her angel surprise cake. At the store, the grocer can't read all of the shopping list, until Max solves the problem by drawing a picture.
"A Max & Ruby picture book"--Cover.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
1.9
K-3
Keywords: Rabbits -- Fiction; Brothers and sisters -- Fiction; Baking -- Fiction; Cake -- Fiction; Rabbits -- Fiction; Siblings -- Fiction; Baking -- Fiction; Cake -- Fiction; Rabbits -- Fiction; Brothers and sisters -- Fiction; Baking -- Fiction; Cake -- Fiction